LncRNAs: Architectural Scaffolds or More Potential Roles in Phase Separation - Luo, Jie; Qu, Lei; Gao, Feiran; Lin, Jun; Liu, Jian; Lin, Aifu (Frontiers in Genetics, 2021)
Biomolecules specifically aggregate in cytoplasm and nucleus, driving liquid-liquid phase separation (LLPS) formation and diverse biological processes. Extensive studies have focused on revealing multiple functional membraneless organelles in both nucleus and cytoplasm. Condensation compositions of LLPS, such as proteins and RNAs affecting the formation of phase separation, have been gradually unveiled. LncRNAs possessing abundant second structures usually promote phase separation formation by providing architectural scaffolds for diverse RNAs and proteins interaction in both nucleus and cytoplasm. Beyond scaffolds, lncRNAs may possess more diverse functions, such as functioning as enhancer RNAs or buffer. In this review, we summarized current studies on the function of phase separation and its related lncRNAs, mainly in the nucleus. This review will facilitate our understanding of the formation and function of phase separation and the role of lncRNAs in these processes and related biological activities. A deeper understanding of the formation and maintaining of phase separation will be beneficial for disease diagnosis and treatment.